Convection-induced anisotropy in excitable media subject to solenoidal advective flow fields - Ramos, J.I. (Chaos, solitons and fractals, 2001)
The effects of solenoidal velocity fields on the propagation of spiral waves in excitable media is studied numerically by means of a time-linearized method. It is shown that the advective field distorts the spiral wave at moderate frequencies, whereas, at large frequencies, the average shape of the spiral wave is nearly identical to that in the absence of convection, although its inner and outer parts exhibit spatial oscillations whose frequency increases as that of the velocity field is increased. At low frequencies and high amplitudes of the velocity field, the concentration of the activator and the wave propagation are controlled by the symmetry of the velocity and the number and location of the stagnation points, and the concentration of the activator may exhibit either counter-rotating regions or a layered structure.